1993
DOI: 10.1111/j.1365-2621.1993.tb04291.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus acidilactici PO2 Bacteriocin Production in Whey Permeate and Inhibition of Listeria monocyfogenes in Foods

Abstract: Growth of Pediococcus acidiluctici PO2 and production of associated bacteriocin (pediocin P02) were demonstrated in whey permeate (WP) supplemented with 0.54% yeast extract (YE). Initial pH 6.5 (without Pfi*regulation during fermentation) wag optimal fo; production of uediocin PO2 in WP containing 2% YE. A oediocin-rich dairy inurehient (PRDI) powder was mad'e of the fermented WP and ap&iei in heat-treated whole milk and pasteurized liquid whole egg. PRDI inhibited Lisferia monocyfogenes in milk. L. tnonocyfog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Also Guerra and Pastrana (2002) found that the nisin and pediocin produced by Lactococcus lactis and Pediococcus acidilactici obtained on whey were lower than those obtained on MRS broth. The same observation was reported by Liao et al (1993) experimenting with L. plantarum UG1 when grown in whey permeates producing plantaricin UG1. Few publications also reported the feasibility of the production of both nisin and pediocin AcH bacteriocins in whey permeate.…”
Section: Discussionsupporting
confidence: 86%
“…Also Guerra and Pastrana (2002) found that the nisin and pediocin produced by Lactococcus lactis and Pediococcus acidilactici obtained on whey were lower than those obtained on MRS broth. The same observation was reported by Liao et al (1993) experimenting with L. plantarum UG1 when grown in whey permeates producing plantaricin UG1. Few publications also reported the feasibility of the production of both nisin and pediocin AcH bacteriocins in whey permeate.…”
Section: Discussionsupporting
confidence: 86%
“…However, Philp & Co. Ltd, under the Generic Industry Research and re-growth of Listeria occurred within 24 h. A Listeria popuDevelopment Biotechnology Program. lation-dependent inhibitory effect combined with reinitiation of growth upon extended incubation was also observed with pediocin PO2 (Liao et al 1993), pediocin 5…”
mentioning
confidence: 67%
“…Therefore, condition that promote higher cell density, usually result in greater bacteriocin production. This growth-bacteriocin association was observed in cultures producing nisin [29,34,35], pediocin PO2 [30], pediocin AcH [47], leuconosin S [48], sakacin A [47], and bavaricin [49]. Maximal bacteriocin production corresponds to the late exponential or early stationary growth phase [30,48] and maximum cell concentration [50,51].…”
Section: Discussionmentioning
confidence: 98%
“…These researchers indicated that whey supported the growth and bacteriocin production, but biomass and bacteriocin levels were lower than those obtained in MRS broth. Liao et al [30] also studied the production of pediocin from whey permeate. According to these researchers, whey permeate supports pediocin production when the medium is supplemented with yeast extract.…”
Section: Introductionmentioning
confidence: 97%